2020
DOI: 10.3390/jcm9062005
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorocholine PET and Multiphase CT Integrated in Dual Modality PET/4D-CT for Preoperative Evaluation of Primary Hyperparathyroidism

Abstract: The present retrospective study evaluates the diagnostic value of integrated 18F-Fluorocholine positron emission tomography/four-dimensional contrast-enhanced computed tomography (18F-FCH PET/4D-CT) as second-line imaging in preoperative work-up of primary hyperparathyroidism (pHPT), and compares 18F-FCH PET with 4D-CT. Patients with pHPT and negative/discordant first-line imaging addressed for integrated 18F-FCH PET/4D-CT were retrospectively selected. Sensitivity and detection rate (DR%) of 18F-FCH PET/CT, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 33 publications
(38 reference statements)
0
32
1
Order By: Relevance
“…Two recent studies combined FCH PET and 4D-CT for integrated fusion imaging, with high sensitivity of 93-100%. In one study, combined FCH PET/4D-CT was shown to be more sensitive than either modality alone [89], while another study showed that combined FCH PET/4D-CT was more sensitive than 4D-CT alone but was equivalent to FCH PET alone [90]. FCH PET had a higher sensitivity than 4D-CT when directly compared [90].…”
Section: Choline Pet/ctmentioning
confidence: 99%
“…Two recent studies combined FCH PET and 4D-CT for integrated fusion imaging, with high sensitivity of 93-100%. In one study, combined FCH PET/4D-CT was shown to be more sensitive than either modality alone [89], while another study showed that combined FCH PET/4D-CT was more sensitive than 4D-CT alone but was equivalent to FCH PET alone [90]. FCH PET had a higher sensitivity than 4D-CT when directly compared [90].…”
Section: Choline Pet/ctmentioning
confidence: 99%
“…Finally, two studies compared [ 18 F]FCH PET with 4DCeCT, a method that provides both functional and anatomical information thanks to the addition of the fourth dimension consisting of changes in contrast attenuation over time [39]. It was shown that [ 18 F]FCH PET/CT and 4DCeCT had quite similar detection rates (57% and 55%, respectively) and sensitivities (81% and 74%, respectively) and, consequently, integrated [ 18 F]FCH PET/4DCeCT could yield the highest reliability (73% detection rate and 100% sensitivity) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, 100 duplicate articles as well 92 studies, including 33 not in the field of interest, 8 case reports, 31 abstracts, 15 reviews, one editorial, three congress and meetings, and one without full text were excluded. Among the remaining 46 articles, 16 [11][12][13][20][21][22][23][24][25][26][27][28][29][30][31][32] finally met the inclusion criteria and were subsequently included in our analysis. A flow diagram of eligible literature is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%